Skor Pengetahuan SPO Pemasangan Kateter pada Mahasiswa Sebelum dan Sesudah Demonstrasi Melalui Zoom Meetings - Wieda Widyatry Qarragita; Iin Inayah; Murtiningsih Murtiningsih; Hasbi Taobah Ramdani (STIKes Karsa Husada Garut, 2021)
Various changes in learning methods have been made so that learning objectives can be achieved during this pandemic, one of which is by doing bold learning, so that some e-learning platforms become part that cannot be used, one of which is using the Zoom meeting application. Through zoom meetings, teachers will not only deliver material through power points or lectures, but will also demonstrate by directly interacting with students even though they are not face-to-face, one of which is nursing care material with catheter insertion. The purpose of this study was to find out about the standard procedure (SOP) for catheter insertion before and before the demonstration through a zoom meeting. This research was conducted in a nursing laboratory involving as many as 102 students from the D3 Nursing program. The method used is quantitative to see how big the difference in scores is before and after the demonstration using zoom meetings. The results of the study show that there is an increase in the average score from 30.09 to 70.11 so that it can be seen that the launch of the installation SPO through Zoom meeting can increase student scores